Water treatment waste: comparison between sedimentation and flotation for sludge thickening at a Brazilian water treatment plant. (28th July 2022) - Hedlund, Keila Fernanda Soares; Maraschin, Manoel; Schneider, Ivo André Homrich; Moraes, Beatriz Stoll; Somavilla, Ezequiel; Carissimi, Elvis
Water treatment plants (WTPs) are essential for the production of potable water. However, they produce large amounts of waste that must be treated and disposed of properly. Thickening is the prior step and most important phase for sludge disposal or even reuse. This study evaluated the thickening of the sludge of a WTP by sedimentation and dissolved air flotation (DAF), using anionic, non-ionic, and cationic polymers, with dosages ranging from 0 to 5.5 mg polymer/g TSS. The parameters evaluated after thickening were: turbidity of the clarified water; concentration of solids and filtration resistance, of thickened the sludge. DAF thickening resulted in lesser turbidity in the clarified water (23.3 NTU) when compared to sedimentation (46.3 NTU). The highest solids concentration was found in the sludge thickened by sedimentation (7.10%). Sedimentation thickening resulted in sludge with a smaller filtration resistance (9.0E + 12 m.kg -1 ) than flotation (10.9E + 12 m.kg -1 ). In comparison with thickening, sedimentation proved to be a more promising alternative, showing better results regarding solids concentration and filtration resistance, thus being a good treatment alternative to avoid undue disposal of this residue.